Why Developing Countries are at Disadvantage Position in WTO Dispute Settlement Mechanism - Waqas, Muhammad (International Journal of Social Sciences and Management, 2014)
The Dispute Settlement Board of WTO aims to solve the disputes of WTO members regarding international trade. Dispute settlement process involves the parties and third parties to a case, and it operates through the DSB panels, the Appellate Body, the WTO Secretariat, arbitrators, independent experts and several specialized institutions. Although the dispute settlement mechanism provides opportunities to the developing countries to seek remedies if they are aggrieved by any other country, yet there are certain challenges for the developing countries to participate effectively in DSM. The study finds out the challenges that caused the role of developing countries less significant in the WTO dispute settlement process. Moreover, several recommendations have also been made for making the role of developing countries more effective. DOI: http://dx.doi.org/10.3126/ijssm.v1i2.10103 Int. J. Soc. Sci. Manage. Vol-1, issue-2: 60-63